DAMPAK KECANDUAN GAME ONLINE TERHADAP SISWA KELAS X IPS DI SMA PGRI PEKANBARU - Ashram, Syarief Maulana; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the academic, financial, health and psychological impact of students who are addicted to online games at SMA PGRI Pekanbaru. This type of research is qualitative research. The measuring instrument used in this study is a scale of measuring the impact of students' online game addiction which consists of 50 items before validation, and after validation, 43 items are obtained with validity of 0.5255 and reliability of 0.918. The research subjects were 7 students who were identified as having a level of addiction to online games. The data analysis technique used is the percentage formula.Key Words: Impact Of Online Games